Krüppel-Like Factors in Metabolic Homeostasis and Cardiometabolic Disease - Oishi, Yumiko; Manabe, Ichiro (Frontiers in Cardiovascular Medicine, 2018)
Members of the Krüppel-like factor (KLF) family of transcription factors, which are characterized by the presence of three conserved Cys2/His2 zinc-fingers in their C terminal domains, control a wide variety of biological processes. In particular, recent studies have revealed that KLFs play diverse and essential roles in the control of metabolism at the cellular, tissue and systemic levels. In both liver and skeletal muscle, KLFs control glucose, lipid and amino acid metabolism so as to coordinate systemic metabolism in the steady state and in the face of metabolic stresses, such as fasting. The functions of KLFs within metabolic tissues are also important contributors to the responses to injury and inflammation within those tissues. KLFs also control the function of immune cells, such as macrophages, which are involved in the inflammatory processes underlying both cardiovascular and metabolic diseases. This review focuses mainly on the physiological and pathological functions of KLFs in the liver and skeletal muscle. The involvement of KLFs in inflammation in these tissues is also summarized. We then discuss the implications of KLFs’ control of metabolism and inflammation in cardiometabolic diseases.